Multisite Reproducibility of the Broth Microdilution Method for Susceptibility Testing of Nocardia Species - Patricia S. Conville; Barbara A. Brown‐Elliott; Richard J. Wallace; Frank G. Witebsky; Deloris E. Koziol; Geraldine S. Hall; S. B. Killian; Cindy C. Knapp; David M. Warshauer; Tam T. Van; Nancy L. Wengenack; Sharon M. Deml; et al. (2012)
ABSTRACT Antimicrobial susceptibility testing (AST) of clinical isolates of Nocardia is recommended to detect resistance to commonly used antimicrobial agents; such testing is complicated by difficulties in inoculum preparation and test interpretation. In this study, six laboratories performed repetitive broth microdilution testing on single strains of Nocardia brasiliensis , Nocardia cyriacigeorgica , Nocardia farcinica , Nocardia nova , and Nocardia wallacei . For each isolate, a total of 30 microdilution panels from three different lots were tested at most sites. The goal of the study was to determine the inter- and intralaboratory reproducibility of susceptibility testing of this group of isolates. Acceptable agreement (>90% agreement at ±1 dilution of the MIC mode) was found for amikacin, ciprofloxacin, clarithromycin, and moxifloxacin. After eliminating MIC values from single laboratories whose results showed the greatest deviation from those of the remaining laboratories, acceptable agreement was also found for amoxicillin-clavulanic acid, linezolid, minocycline, and tobramycin. Results showed unsatisfactory reproducibility of broth microdilution testing of ceftriaxone with N. cyriacigeorgica and N. wallacei , tigecycline with N. brasiliensis and N. cyriacigeorgica , and sulfonamides with N. farcinica and N. wallacei. N. nova ATCC BAA-2227 is proposed as a quality control organism for AST of Nocardia sp., and the use of a disk diffusion test for sulfisoxazole is proposed as a check of the adequacy of the inoculum and to confirm sulfonamide MIC results.